Addition of Dairy Lipids and Probiotic Lactobacillus fermentum in Infant Formulas Modulates Proteolysis and Lipolysis With Moderate Consequences on Gut Physiology and Metabolism in Yucatan Piglets - Lemaire, Marion; Ménard, Olivia; Cahu, Armelle; Nogret, Isabelle; Briard-Bion, Valérie; Cudennec, Benoit; Cuinet, Isabelle; Le Ruyet, Pascale; Baudry, Charlotte; Dupont, Didier; Blat, Sophie; Deglaire, Amélie; et al. (Frontiers in Nutrition, 2021)
Breast milk is the gold standard in neonatal nutrition but most infants are fed infant formulas in which lipids are usually of plant origin. The addition of dairy lipids and/or milk fat globule membrane (MFGM) extracts in formulas improve their composition with beneficial consequences on protein digestion. The probiotic Lactobacillus fermentum (Lf) was reported to reduce transit time in rat pups, which may also favour digestion. This study aimed to investigate the effects of the addition of dairy lipids in formulas, with or without Lf, on protein and lipid digestion and on gut physiology. Piglets were suckled from postnatal day 2 to 28 with formulas containing either plant lipids (PL), a half-half mixture of plant and dairy lipids (DL), or this mixture supplemented with Lf (DL+Lf). At day 28, piglets were euthanized 90 min after their last feeding. Microstructure of digesta did not differ among formulas. Gastric proteolysis was increased (P < 0.01) in DL and DL+Lf (21.9 ± 2.1% and 22.6 ± 1.3 %, respectively) compared with PL (17.3 ± 0.6 %) and the residual proportion of gastric intact caseins decreased (P < 0.01) in DL+Lf (5.4 ± 2.5 %) compared with PL and DL (10.6 ± 3.1 % and 21.8 ± 6.8 %, respectively). Peptide diversity in ileum and colon was lower in PL compared to DL and DL+Lf. DL and DL+Lf displayed an increased (P < 0.01) proportion of diacylglycerol/cholesterol in jejunum and ileum compared to PL and tended (P = 0.07) to have lower triglyceride/total lipids ratio in ileum DL+Lf (0.019 ± 0.003) as compared to PL (0.045 ± 0.011). The percentage of endocrine tissue and the number of islets in pancreas were decreased (P < 0.05) in DL+Lf compared with DL. DL+Lf displayed a beneficial effect on host defences (increased goblet cell density in jejunum (P < 0.05) and a trophic effect (increased duodenal (P = 0.09) and jejunal (P < 0.05) weights). Altogether, our results demonstrate that addition of dairy lipids and probiotic Lf in infant formula modulated protein and lipid digestion, with consequences on lipid profile and with beneficial, though moderate, physiological effects